2021
DOI: 10.1111/gcb.15579
|View full text |Cite
|
Sign up to set email alerts
|

Building a bridge between adaptive capacity and adaptive potential to understand responses to environmental change

Abstract: Adaptive capacity is a topic at the forefront of environmental change research with roots in both social, ecological, and evolutionary science. It is closely related to the evolutionary biology concept of adaptive potential. In this systematic literature review, we: (1) summarize the history of these topics and related fields; (2) assess relationship(s) between the concepts among disciplines and the use of the terms in climate change research, and evaluate methodologies, metrics, taxa biases, and the geographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 87 publications
(129 reference statements)
0
12
0
Order By: Relevance
“…But introducing more variability between populations in their demographic dynamics (e.g., unstable trends) or in their phenotypic and genotypic composition would open up new perspectives to better address the portfolio effect. However, we found that intrapopulation genetic variance was enhanced in sink populations receiving immigrants from nearby populations, potentially increasing adaptive capacity (Jump et al 2009, Seaborn et al 2021).…”
Section: Evidence Of a Non-linear Relationship Between Dispersal And ...mentioning
confidence: 80%
“…But introducing more variability between populations in their demographic dynamics (e.g., unstable trends) or in their phenotypic and genotypic composition would open up new perspectives to better address the portfolio effect. However, we found that intrapopulation genetic variance was enhanced in sink populations receiving immigrants from nearby populations, potentially increasing adaptive capacity (Jump et al 2009, Seaborn et al 2021).…”
Section: Evidence Of a Non-linear Relationship Between Dispersal And ...mentioning
confidence: 80%
“…Lastly, socioeconomic adaptive capacity depicts people's ability to anticipate and respond to changes, and to minimize, cope with and recover from climate change impacts (Adger & Vincent, 2005; Cinner et al, 2013). This domain obtained the greatest number of applications in peer‐reviewed literature ( n = 312; Figure 5d,e), partly due to its nature that is closely related to the responses of human systems and its potential to transfer analysis into climate change adaptation effort (Seaborn et al, 2021; Siders, 2019). We identified 53 indicators and classified them into six subgroups, including learning, assets, demographics and social settings, governance, social organizations, and flexibility.…”
Section: Resultsmentioning
confidence: 99%
“…The metrics of genomic vulnerability estimated here are therefore reliable and have clear implications for not only delineating future conservation units but also informing management decisions of this key long-lived tree species 49 . For instance, the southeastern populations nearby the Korean Peninsula are inferred to be most at risk from future higher temperatures and more intense precipitation.…”
Section: Genomic Vulnerability Prediction To Future Climate Changementioning
confidence: 88%